Analisis Radiografi Sinar-X Terhadap Sambungan Pelat Baja Tahan Karat Aisi 304 Hasil Pengelasan Tungsten Inert Gas Dengan Arus 40–60 Ampere - Sungkono; Cahyono HP; ahmad zayadi (FTK UNSURYA, 2021)
X-Ray Radiographic Analysis of Aisi 304 Stainless Steel Plate Joints From Inert Gas Tungsten Welding Results with 40 – 60 Ampere Current. Metal welding process is one of the main processes in machine construction. The quality of welded joints determines the strength and toughness of a machine construction. The quality of welded joints of installed construction can be determined by the non-destructive test method using X-ray radiography equipment. This study aims to obtain a butt joint obtained from TIG welding of AISI 304 stainless steel plate with a current of 40 - 60 A, identification of defects in the 1G butt joint, and analysis of the quality of the weld joint. The research method used is testing of welded joints using X-ray radiography which refers to the ASME V article II standard and the connection quality refers to ASME section IX. The results showed that TIG welding with a current of 60 Ampere produced a butt joint butt joint that was penetrated and there was no gap between the plates, whereas with a current of 40 A and 50 A the weld joint was not see-through but there was still a gap between the plates. Incomplete penetration weld defects were found in the welded SS 304 plate joints with a current of 40 A. Welded porosity defects were found in the welded SS 304 plate joints with a current of 50 A. Weld defects were not found in the SS 304 plate joints with a current of 60 A. Butt joint connections TIG welded SS 304 plate with the best current of 60 A compared to the current of 40 A and 50 A.